Implementasi Supervisi Pendidikan Dalam Meningkatkan Profesionalisme Guru Di Madrasah Ibtidaiyah - Ashshiddiqi, Muhammad Hasbie (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
Teacher professionalism is a fundamental aspect in realizing superior quality education in Madrasah Ibtidaiyah. However, many teachers still face challenges in improving their competence in a sustainable manner. One strategy that can be optimized to overcome this problem is through the implementation of effective educational supervision by the head of the madrasah. This study aims to describe and analyze the implementation of educational supervision in improving teacher professionalism in Madrasah Ibtidaiyah. This study uses a qualitative approach with a type of literature and field study, where primary data is obtained through interviews, observations, and documentation from the head of the madrasah and teachers. While secondary data is collected from scientific journals, books, and educational policy documents. The data analysis technique uses the Miles and Huberman interactive model, and the validity of the data is guaranteed through triangulation of sources and techniques. The results of the study indicate that educational supervision that is systematically designed and implemented with a communicative approach has a significant impact on improving the pedagogical, professional, social, and personality competencies of teachers. Supervision that is not judgmental but more towards collective coaching can increase teacher motivation and self-confidence. This study also found that relational factors such as effective communication and trust between the principal and teachers play a major role in the success of supervision. The implications of this study encourage the need for supervision training based on a humanistic approach in order to create a culture of supervision that supports the continuous professional development of teachers.